KONTRIBUSI IKLIM KERJA, KESEJAHTERAAN GURU DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA GURU SLB SE-KABUPATEN KULON PROGO TAHUN 2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The purposes of this research are to find out the contribution of working climate, teacher’s prosperity and working motivation simultaneously to the teachers working productivity of special school in Kulon Progo regency, find out the contribution of working climate, teacher’s prosperity and working motivation to the teachers working productivity of special school of Kulon Progo regency partially.The Population of this research were all of special school teachers in Kulon Progo Regency which totally 130 persons. The sample was 95 person which was taken by Nomogram Harry King formula at the 5 % signification with Proportionate Random Sampling technique. In collecting data the researcher used questionnare and documentation. The analysis technique used multiple regression and partial correlation with level significantly is 5%.The result of the research showed that the working climate, teacher’s prosperity and working motivation have positive contribution that significant simultaneously to the teachers working productivity of special school of kulon progo regency. The effectivity contribution of working climate, teacher’s prosperity and working motivation to the teachers working productivity is 68,9 %, thus the number 31,1% cannot be explained at this research caused by anathor factor. The relative contribution of working climate gave 60,43%, relative contribution of teacher’s prosperity gave 1,31%, and relative contribution of working motivation gave 38,26% whereas, the number of effective contribution to each free variable at the bound is 41,63% for the working climate, 0,90% for the teacher’s prosperity and 26,36% for working motivation. The school climate had positive and significant contribution to the working productivity of special school of kulon progo regency. The teacher’s prosperity had not positive and significant contribution to the working productivity of special school of kulon progo regency. The working motivation had positive and significant contribution o the working productivity of special school of kulon progo regency.